Effects of Bile Acids and Nisin on the Production of Enterotoxin by Clostridium perfringens in a Nutrient-Rich Medium - Miseon Park; Fatemeh Rafii (International Journal of Microbiology)
Clostridium perfringens is the second most common cause of bacterial foodborne illness in the United States, with nearly a million cases each year. C. perfringens enterotoxin (CPE), produced during sporulation, damages intestinal epithelial cells by pore formation, which results in watery diarrhea. The effects of low concentrations of nisin and bile acids on sporulation and toxin production were investigated in C. perfringens SM101, which carries an enterotoxin gene on the chromosome, in a nutrient-rich medium. Bile acids and nisin increased production of enterotoxin in cultures; bile acids had the highest effect. Both compounds stimulated the transcription of enterotoxin and sporulation-related genes and production of spores during the early growth phase. They also delayed spore outgrowth and nisin was more inhibitory. Bile acids and nisin enhanced enterotoxin production in some but not all other C. perfringens isolates tested. Low concentrations of bile acids and nisin may act as a stress signal for the initiation of sporulation and the early transcription of sporulation-related genes in some strains of C. perfringens, which may result in increased strain-specific production of enterotoxin in those strains. This is the first report showing that nisin and bile acids stimulated the transcription of enterotoxin and sporulation-related genes in a nutrient-rich bacterial culture medium.